Exploring Occupational and Behavioral Risk Factors for Obesity in Firefighters: A Theoretical Framework and Study Design - BongKyoo Choi; Peter Schnall; Marnie Dobson; Leslie Israel; Paul Landsbergis; Pietro Galassetti; Andria Pontello; Stacey Kojaku; Dean Baker (Elsevier, 2011)
Firefighters and police officers have the third highest prevalence of obesity among 41 male occupational groups in the United States (US). However, few studies have examined the relationship of firefighter working conditions and health behaviors with obesity. This paper presents a theoretical framework describing the relationship between working conditions, health behaviors, and obesity in firefighters. In addition, the paper describes a detailed study plan for exploring the role of occupational and behavioral risk factors in the development of obesity in firefighters enrolled in the Orange County Fire Authority Wellness Fitness Program. The study plan will be described with emphasis on its methodological merits: adopting a participatory action research approach, developing a firefighter-specific work and health questionnaire, conducting both a cross-sectional epidemiological study using the questionnaire and a sub-study to assess the validity of the questionnaire with dietary intake and physical activity measures, and evaluating the strengths and weaknesses of the body mass index as an obesity measure in comparison to skinfold-based percent body fat. The study plan based on a theoretical framework can be an essential first step for establishing effective intervention programs for obesity among professional and voluntary firefighters.